2018
DOI: 10.1183/13993003.02055-2017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 100% oxygen on breathing pattern are not limited to young children

Abstract: Breathing 100% oxygen has been reported to decrease tidal volume (VT) in infants [1] and recent evidence published in the European Respiratory Journal suggest that transient less pronounced effects are also seen in preschool children [2]. It is unclear whether there is an age dependency beyond infancy in the response to 100% oxygen or whether it is limited to young children. Here we investigate the effects of 100% oxygen on breathing pattern across a spectrum of ages to identify the change in VT that occurs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Taking all into account, it seems unlikely that the different software versions used in our study with their inherent algorithms to process signals to MBW parameters are a major determinant contributing to differences between N 2 -and SF 6 -LCI observed. Some studies detected a decrease in VT during inhalation of 100% O 2 in infants, preschool children, and even young adults of up to 29 years [34,[42][43][44]. However, these studies observed a minimal effect on breathing pattern after early infancy, which is in line with our study in older infants and children demonstrating no difference in VT and RR between N 2 -and SF 6 -MBW (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Taking all into account, it seems unlikely that the different software versions used in our study with their inherent algorithms to process signals to MBW parameters are a major determinant contributing to differences between N 2 -and SF 6 -LCI observed. Some studies detected a decrease in VT during inhalation of 100% O 2 in infants, preschool children, and even young adults of up to 29 years [34,[42][43][44]. However, these studies observed a minimal effect on breathing pattern after early infancy, which is in line with our study in older infants and children demonstrating no difference in VT and RR between N 2 -and SF 6 -MBW (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Although we previously identified NBD as one factor (19) contributing to the differences between the two methodologies, we have speculated that NBD alone may be inadequate to account fully for the differences. Other studies (13,17,19,21) have also demonstrated a significant effect of NBD on N 2 washout kinetics, but other factors such as the use of 100% oxygen for washout (16) may also contribute to the difference between SF 6 and N 2 washout kinetics.…”
Section: Discussionmentioning
confidence: 94%
“…For example, the individual systems normally use different washout gases (100% O2 vs. air). A recent study (16) has reported a considerable effect on breathing pattern (lower tidal volume) of 100% oxygen in all age groups, which may affect CEV and LCI. Furthermore, it remains unknown whether there is an influence of pure oxygen on gas exchange.…”
Section: Discussionmentioning
confidence: 96%